Seed bank characteristics in a Pinus densata forest and its relationship with vegetation diversity in Southeast Tibet, China. Issue 17 (20th August 2020) - Lu, Jie; Li, Zhaoqing; Gao, Tan; Tang, Xiaoqin
Abstract: Objective: We aimed to understand the basic characteristics of the underground seed bank of Pinus densata forest and its relationship with aboveground vegetation, to provide a theoretical basis for vegetation restoration. Methods: The study sites were Dongjiu Bridge (DJ), Linji Bridge (LZ), and Birishen Mountain Scenic Spot (RB) in Gongbu Nature Reserve, Southeast Tibet, China. Species composition and distribution pattern of the underground seed bank in P . densata forest were analyzed. Germination data and field investigations were used to examine the similarities between aboveground vegetation and underground seed banks, and their responses to the environment. Results: There were 47 species belonging to 27 families in the underground seed bank of the P. densata forest. Asteraceae, Rosaceae, Labiatae, and Poaceae were dominant, accounting for 40.4% of the total number of families. Underground seed density was 2, 114, 1, 952, and 1, 141 seeds/m 2 in DJ, LZ, and BR, respectively. The percentage of different life‐forms in each sampling location was shown to be perennial herbs > shrubs > annual herbs > trees > subshrubs. The Shannon–Wiener diversity index, Margalef richness index, and Simpson's dominance index of each sample showed that species decreased with higher elevation, while the Pielou evenness index showed the opposite trend. Elevation, slope position, slope aspect, and slope were positively correlated with the Pielou evenness index and negatively correlated with the Shannon–Wiener diversity index, Margalef richness index, and Simpson's dominance index. The Sørensen index, comparing the similarity between the underground seed bank and aboveground vegetation of DJ, LZ, and BR was 0.46, 0.35, and 0.31, respectively. Conclusion: The underground seed bank of P .  densata forest has high seed density and high species richness, but there was little similarity between aboveground vegetation and underground seed bank. Elevation and slope position had a great influence on the uniformity of species distribution. Abstract : Compositae, Rosaceae, Labiatae, and Gramineae as dominant species accounted for 40.42% of the total species. Percentage of different life‐forms in each sampling location was shown as perennial herb > shrub > annual herb > tree > subshrub. The elevation and slope position had great influence on the uniformity of species distribution.